Nuances de la littérature populaire et de la culture populaire sur le développement social - bouchelaleg, abdelziz; souisi, nassira (Journal of Social Sciences and Humanities, 2021)
Popular culture is linked to popular literature, which leaves it having an impact on behavior and social relationships and thus contributes to social development. It does not mean the association with inheritance and the set of customs and traditions of a particular group, but it has an impact on aspects of human life, because in fact it does not start from data related to the accumulation of knowledge and information, and is based on the living and moving attitudes it creates in the social environment. All of this makes it a contribution to social development, with the tools of expression that popular literature takes as an effective means of reaching this goal. It is also a source of development, a path to progress and prosperity, through the summoning of the past and the partiality of inheritance. Let man begin to establish his ideas and perceptions on the ground, in behavioral and relational stereotypes, in accordance with the ability of popular culture to think, and leave him distinguished and able to criticize, moral commitment and ability to choose.